WHO/ILO work-related burden of disease and injury: Protocol for systematic reviews of exposure to long working hours and of the effect of exposure to long working hours on alcohol consumption and alcohol use disorders. (November 2018) - Godderis, Lode; Boonen, Emma; Cabrera Martimbianco, Ana L.; Delvaux, Ellen; Ivanov, Ivan D.; Lambrechts, Marie-Claire; Latorraca, Carolina O.C.; Leppink, Nancy; Pega, Frank; Prüss-Ustün, Annette M.; Riera, Rachel; Ujita, Yuka; et al.
Abstract: Background: The World Health Organization (WHO) and the International Labour Organization (ILO) are developing a joint methodology for estimating the national and global work-related burden of disease and injury (WHO/ILO joint methodology), with contributions from a large network of experts. In this paper, we present the protocol for two systematic reviews of parameters for estimating the number of deaths and disability-adjusted life years from alcohol consumption and alcohol use disorder attributable to exposure to long working hours, to inform the development of the WHO/ILO joint methodology. Objectives: We aim to systematically review studies on exposure to long working hours (Systematic Review 1) and systematically review and meta-analyse estimates of the effect of exposure to long working hours on alcohol consumption and alcohol use disorder (Systematic Review 2), applying the Navigation Guide systematic review methodology as an organizing framework. Data sources: Separately for Systematic Reviews 1 and 2, we will search electronic academic databases for potentially relevant records from published and unpublished studies, including MEDLINE, Embase, Web of Science, CISDOC and PsychINFO. We will also search electronic grey literature databases, Internet search engines and organizational websites; hand-search reference list of previous systematic reviews and included study records; and consult additional experts. Study eligibility and criteria: We will include working-age (≥15 years) workers in the formal and informal economy in any WHO and/or ILO Member State but exclude children (<15 years) and unpaid domestic workers. For Systematic Review 1, we will include quantitative prevalence studies of relevant levels of exposure to long working hours (i.e., 35–40, 41–48, 49–54 and ≥55 h/week) stratified by country, sex, age and industrial sector or occupation. For Systematic Review 2, we will include randomized controlled trials, cohort studies, case-control studies and other non-randomized intervention studies with an estimate of the relative effect of a relevant level of exposure to long working hours on total amount of alcohol consumed and on the incidence of, prevalence of or mortality from alcohol use disorders, compared with the theoretical minimum risk exposure level (i.e., worked 35–40 h/week). Study appraisal and synthesis methods: At least two review authors will independently screen titles and abstracts at a first stage and full texts of potentially eligible records at a second stage, followed by extraction of data from qualifying studies. At least two review authors will assess risk of bias and quality of evidence, using the most suited tools currently available. For Systematic Review 2, if feasible, we will combine relative risks using meta-analysis. We will report results using the guidelines for accurate and transparent health estimates reporting (GATHER) for Systematic Review 1 and the preferred reporting items for systematic reviews and meta-analyses guidelines (PRISMA) for Systematic Review 2. PROSPERO registration number : CRD42018084077. Highlights: Long working hours have been associated with increased alcohol consumption. We report the protocol for a systematic review on the topic. The methodology for the systematic review is explained in detail. This research is part of the joint methodology of the WHO and ILO.